Context Analysis of Advertising Design: A New Context-Based Semiotic Approach - Safavi, Sarvenaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This research tried to validate a new approach to semiotic analysis in advertising posters. The aim of writing this thesis was to reveal a new approach in dealing with signs and the way it is used in advertising design. Due to the nature of advertising designs they are constructed on the selection and combination of signs and because of this, people can also select and perceive some of the signs in advertisings posters. Based on the results, it is possible to say that there are no absolute parameters to design an advertising poster in which all the receivers will have the same understanding. Designers aren’t the only ones that will select and combine signs also readers of the text follow the same procedure in order to read the signs. These differences in interpretation is based on the differentiation of understanding Context B and the Context C of each receiver which is due to the information available from the individual perception of the so-called Context B and Context C. Based on the results and findings of this research, the researcher has proven that not only the human perception is different from individual to individual in advertising posters, also it is depended on the three context which the researcher called Context A the linguistic context, Context B the situational context and Context C which is the background knowledge of each individual. These variations in interpretation and perception of advertising posters have three main reasons that can be concluded as three contexts. Some people do not select and perceive all the sentences, including linguistics and/or non-linguistics sentences. The difference in the situational context can be the reason of reading the text in different ways, due to the fact that the knowledge of individuals can be different, consciously and/or unconsciously this knowledge can affect the way that an individual read and understand a advertising posters. Keywords: Semiotics, Context, Advertising Design, Human Perception.

ÖZ: Bu araştırma, reklam posterlerinde göstergebilim analizine yeni bir yaklaşımı doğrulamaya çalışmıştır. Bu tezin yazılma amacı işaretlerin kullanımı ile ilgili yeni bir yöntemin reklam tasarımında nasıl kullanılabileceğini ortaya koymaktır. Reklamın doğal yapısından ötürü reklam posterinin yapımı tamamen göstergelerin seçimi ve birleşimi üzerinden oluşmaktadır. Bu nedenle de kişiler reklam posterindeki göstergeleri seçerek algılamaktadır. Araştırmanın sonuçlarına baktığımızda reklam posterlerinde kesin bir algılama ve anlama yaratmak mümkün değildir. Bu, kişilerin algılarının farklılıklarından oluşan bir durumdur. Sadece tasarımcılar seçim ve birleşim sürecinden geçmezler. Bu süreçte metni okuyan kişiler de okumak ve anlamak için göstergeleri aynı şekilde seçim ve birleşim ile algılamak durumundadır. Yorumlamada ortaya çıkan bu farklar Bağlam B ve Bağlam C’yi anlamakta ortaya çıkan farklardan oluşur. Bir reklam posteri okunurken kişilerin kendi görüşleri Bağlam B ve Bağlam C ile ilişkilendirilir. Bu da demek oluyor ki kişiler Bağlam B ve Bağlam C`yi, Bağlam A ile ilişkilendirerek yorum çıkarır, anlamlandırır. Bağlam C alıcı kişilerin kendilerine özgü yorumlarından oluşur. Bağlam B ve Bağlam C olarak adlandırdığımız bilgi kişilerin kişisel algılarında bulunan yorumlara dayanır. Bu araştırmada bulunan sonuçlar yazarın insan algısında farklılıklar olduğunu ve kişiden kişiye değiştiğini kanıtlamaktadır. Ayrıca yazar bu algının üç bağlama bağlı olduğunu kanıtlar. Bu üç bağlamın birincisi Bağlam A dil bağlamı, ikincisi Bağlam B durumsal Bağlam ve üçüncüsü ise Bağlam C kişilerin kendi geçmişten gelen bilgileridir. Bu reklam posterlerinin yorumlama ve algılamada ortaya çıkan farklılıklarının üç nedeni vardir. Bunun adına Üçlü Bağlamlar denilebilir. Bazı kişiler seçip algılarken bütün cümleyi görmezler buna sözlü ve sözsüz iletişim dahildir. Durumsal Bağlamdan kaynaklı farklılıklar bir metnin okunurken farklı okunmasına yol açmaktadır. Reklam posterini okurken kişilerin bilgisi ve tecrübesi bilinçli veya bilinçsiz bir şekilde algı ve yorumlarını etkileyerek reklam posterinin farklı anlaşılması veya algılanmasına yol açar. Anahtar kelimeler: Göstergebilimi, Bağlam, Reklam Tasarımı, İnsan Algısı.
Doctor of Philosophy in Communication and Media Studies. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2018. Supervisor: Assoc. Prof. Dr. Agah Gümüş.
Keywords: Communication and Media Studies; Semiotics; Context; Advertising Design; Human Perception